Isolation and characterization of exosome-enriched urinary extracellular vesicles from Dent’s disease type 1 Spanish patients - Carla Burballa; Mònica Duran; Cristina Martínez; Gema Ariceta; Gerard Cantero-Recasens; Anna Meseguer (Nefrología (English Edition), 2023)
Background and objectives: Dent's disease type 1 (DD1) is a rare X-linked hereditary pathology caused by CLCN5 mutations that is characterized mainly by proximal tubule dysfunction, hypercalciuria, nephrolithiasis/nephrocalcinosis, progressive chronic kidney disease, and low-weight proteinuria, the molecular hallmark of the disease. Currently, there is no specific curative treatment, only symptomatic and does not prevent the progression of the disease. In this study we have isolated and characterized urinary extracellular vesicles (uEVs) enriched in exosomes that will allow us to identify biomarkers associated with DD1 progression and a better understanding of the pathophysiological bases of the disease. Materials and methods: Through a national call from the Spanish Society of Nephrology (SEN) and the Spanish Society of Pediatric Nephrology (AENP), urine samples were obtained from patients and controls from different Spanish hospitals, which were processed to obtain the uEVS. The data of these patients were provided by the respective nephrologists and/or extracted from the RENALTUBE registry. The uEVs were isolated by ultracentrifugation, morphologically characterized and their protein and microRNA content extracted. Results: 25 patients and 10 controls were recruited, from which the urine was processed to isolate the uEVs. Our results showed that the relative concentration of uEVs/mL is lower in patients compared to controls (0.26 × 106 uEVs/mL vs 1.19 × 106 uEVs/mL, p < 0.01). In addition, the uEVs of the patients were found to be significantly larger than those of the control subjects (mean diameter: 187.8 nm vs 143.6 nm, p < 0.01). Finally, our data demonstrated that RNA had been correctly extracted from both patient and control exosomes. Conclusions: In this work we describe the isolation and characterization of uEVs from patients with Dent 1 disease and healthy controls, that shall be useful for the subsequent study of differentially expressed cargo molecules in this pathology. Resumen: Antecedentes y objetivo: La enfermedad de Dent tipo 1 (DD1) es una patología hereditaria rara ligada al cromosoma X causado por mutaciones en el CLCN5 que se caracteriza principalmente por una disfunción del túbulo proximal, hipercalciuria, nefrolitiasis/nefrocalcinosis, enfermedad renal crónica progresiva y proteinuria de bajo peso molecular, rasgo distintivo de la enfermedad. Actualmente, no existe un tratamiento curativo específico, únicamente sintomático y no previene la progresión de la enfermedad. En este estudio hemos aislado y caracterizado las vesículas extracelulares urinarias (uEVs) enriquecidas en exosomas que nos permitirán identificar biomarcadores asociados a la progresión de DD1 y una mejor comprensión de las bases fisiopatológicas de la misma. Materiales y métodos: A través de una convocatoria nacional de la Sociedad Española de Nefrología (SEN) y la Sociedad Española de Nefrología Pediátrica (AENP), se obtuvieron orinas de pacientes y controles de distintos hospitales españoles, las cuales se procesaron para obtener los uEVS. Los datos de estos pacientes fueron proporcionados por los respectivos nefrólogos y/o extraídos del registro RENALTUBE. Los uEVs se aislaron mediante ultracentrifugación, fueron caracterizados morfológicamente y se extrajo su contenido de proteína y microRNA. Resultados: Se reclutaron 25 pacientes y 10 controles, de los cuales se procesaron las orinas para aislar los uEVs. Nuestros resultados mostraron que la concentración relativa de uEVs/mL es menor en pacientes comparado con controles (0,26 × 106 uEVs/mL vs 1,19 × 106 uEVs/mL, p < 0.01). Además, se vio que los uEVs de los pacientes eran significativamente más grandes que los de los sujetos control (diámetro medio: 187,8 nm vs 143,6 nm, p < 0.01). Finalmente, nuestros datos demostraron que se había extraído correctamente RNA tanto de los exosomas de pacientes como de controles. Conclusiones: En este trabajo describimos el aislamiento y caracterización de uEVs de pacientes de la enfermedad de Dent 1 y controles sanos, útiles para el posterior estudio de moléculas cargo diferencialmente expresadas en esta patología.